2011
DOI: 10.1152/ajpheart.00563.2009
|View full text |Cite
|
Sign up to set email alerts
|

iNOS expression in vascular resident macrophages contributes to circulatory dysfunction of splanchnic vascular smooth muscle contractions in portal hypertensive rats

Abstract: Portal hypertension, a major complication of cirrhosis, is caused by both increased portal blood flow due to arterial vasodilation and augmented intrahepatic vascular resistance due to sinusoidal constriction. In this study, we examined the possible involvement of resident macrophages in the tone regulation of splanchnic blood vessels using bile duct ligated (BDL) portal hypertensive rats and an in vitro organ culture method. In BDL cirrhosis, the number of ED2-positive resident macrophages increased by two- t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Moreover, the enhanced VEGF expression by JAK2/STAT3 signalling, though as an angiogenesis promoter, accelerated intestine inflammation [4]. In addition, high iNOS expression also contributed to the hyperdynamic splanchnic circulation in portal hypertension by regulating splanchnic vascular smooth muscle contractions [34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the enhanced VEGF expression by JAK2/STAT3 signalling, though as an angiogenesis promoter, accelerated intestine inflammation [4]. In addition, high iNOS expression also contributed to the hyperdynamic splanchnic circulation in portal hypertension by regulating splanchnic vascular smooth muscle contractions [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, the initial stimulus (or stimuli) that increase(s) iNOS in hypertensive cutaneous microvasculature remain unclear. Possible candidates include a host of immune modulators including tumor necrosis factor α (TNFα), IL-6, COX-2, and elevated angiotensin II 40 . As such, potential pharmacological targets for the treatment of hypertension-induced microvascular dysfunction include the angiotensin pathway and novel anti-inflammatory compounds such as acromalin which decreases iNOS and COX-2 expression by altering TNFα and IL-6 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Kajita et al[33] observed that iNOS expression in vascular resident macrophages contributed to the circulatory dysfunction of splanchnic vascular smooth muscle contractions in PH rats[33]. Xu et al[34], in a study with male Sprague-Dawley rats submitted to intra-hepatic PH induced by the injection of CCl 4 , noted that iNOS contributes to the haemodynamic alterations of PH secondary to increased levels of NO[34].…”
Section: Discussionmentioning
confidence: 99%